Characterization and Inhibitor Activity of Two Newly Synthesized Thiazole - Omer, Rebaz Anwar; Koparir, Pelin; Ahmed, Lana Omer (Springer Science and Business Media Deutschland GmbH, 2022)
Two noel derivatives of (4-(3-methyl-3-(5,6,7,8-tetrahydronaphthalen-2 yl)cyclobutyl)thiazol-2-yl)glycine and of 2-chloro-N-(4-(3-methyl-3-(5,6,7,8-tetrahydronaphthalen-2yl)cyclobutyl)thiazol-2-yl)acetamide were synthesized. Fourier-Transform Infrared (FT-IR) spectroscopy and Nuclear Magnetic Resonance (NMR) were used to characterize the molecular formula. The different vibrational modes were calculated using Gaussian 09 W software and then corrosion inhibiting activity was determined by the quantum chemical method. In addition, GaussView 5.0 package on B3LYP/6-311G(d,p) method was applied to find the energy of the highest occupied molecular orbital (EHOMO), lowest unoccupied molecular orbital (ELUMO), energy gap (?E = ELUMO?EHOMO), and dipole moment (?), as well as the percent of transmitted electrons (?N). Other molecular properties such as hardness (?), softness (?), and electronegativity (?) were computed based on the results of inhibitor activity. The corrosion inhibiting activities of the derivatives was predicted using quantum chemical calculations. Therefore, the corrosion inhibitor behavior can be expected without an experimental study. The result shows a good relationship between organic-based corrosion inhibitors and the obtained quantum chemical parameters. © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Electronic properties; Organic synthesis; Study of corrosion; Theoretical calculation